The representation of patients with depressive disorder in the narratives by female authors - Siriporn Tansuwan; Krisada Kantichol (Cogent Arts & Humanities, 2025)
This study analyzes the language used in three literary works by women authors through linguistic strategy analysis, narrative analysis, and representation analysis. It explores how language shapes the representation of depression within these narratives. The findings reveal three central themes: (1) the emotional struggles faced by individuals with depression, (2) their perceived divergence from societal norms, and (3) their categorization as deviant by society. These themes construct a portrayal of depression that simultaneously aligns with and challenges dominant social discourses. Notably, the identities of individuals with depression are depicted as emotionally resilient, resisting passive victimhood. By foregrounding these perspectives, the narratives subvert stereotypes and offer alternative representations that emphasize agency and strength. This qualitative approach underscores the capacity of literary texts to foster empathy and deepen public understanding of mental health experiences.